2023
DOI: 10.3390/nano13192679
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional-Printed Vortex Tube Reactor for Continuous Flow Synthesis of Polyglycolic Acid Nanoparticles with High Productivity

Kittipat Suwanpitak,
Pornsak Sriamornsak,
Inderbir Singh
et al.

Abstract: Polyglycolic acid (PGA) nanoparticles show promise in biomedical applications due to their exceptional biocompatibility and biodegradability. These nanoparticles can be readily modified, facilitating targeted drug delivery and promoting specific interactions with diseased tissues or cells, including imaging agents and theranostic approaches. Their potential to advance precision medicine and personalized treatments is evident. However, conventional methods such as emulsification solvent evaporation via batch sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“… 43 The findings of this study align with those of a prior investigation that reported that increased flow rates lead to decreased residence durations, limiting the duration of nucleation and nanoparticle formation. 39 …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“… 43 The findings of this study align with those of a prior investigation that reported that increased flow rates lead to decreased residence durations, limiting the duration of nucleation and nanoparticle formation. 39 …”
Section: Resultsmentioning
confidence: 99%
“…This may be because a total flow rate that is too low or too high and not a proper chitosan and STPP mixing ratio resulted in inconsistent particle formation in the reactor, as reported previously. 39 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations